Multidisciplinary perioperative management of pediatric pheochromocytoma/paraganglioma: a retrospective cohort study with long-term outcomes - Yu, Shenghua; Ren, Lulu; Wei, Sisi; Wang, Guoqing; Ding, Guili; Yu, Yani; Wei, Rong; Zou, Tianxiao (Frontiers in Anesthesiology, 2025)
BackgroundPheochromocytoma and paraganglioma (PPGL) pose significant perioperative challenges in pediatric populations due to catecholamine-driven hemodynamic instability. This study systematically evaluates perioperative management strategies—including preoperative optimization, intraoperative protocols, and postoperative monitoring—to establish evidence-based guidance for improving outcomes in pediatric PPGL surgery.MethodsA single-center retrospective cohort study was conducted at a tertiary specialty hospital from January 2014 to October 2023. Clinical data from eight pediatric PPGL patients undergoing surgical resection were analyzed alongside a synthesis of contemporary literature and consensus guidelines.ResultsAll eight patients received multimodal antihypertensive therapy (phenoxybenzamine, propranolol, and/or calcium channel blockers) for preoperative blood pressure control, achieving normotensive thresholds (<130/80 mmHg). Intraoperative hemodynamic stability was maintained through invasive arterial monitoring and targeted fluid resuscitation, with no hypertensive crises or arrhythmias reported. Postoperatively, normalized urinary vanillylmandelic acid (VMA) levels and blood pressure confirmed biochemical remission. During a median follow-up of 4.5 years (range 7 months–7 years), no instances of tumor recurrence or metastasis were identified.ConclusionsProtocolized perioperative care incorporating α-adrenergic blockade, real-time hemodynamic monitoring, and comprehensive biochemical surveillance ensures safe tumor resection and mitigates surgical risks in pediatric PPGL. These findings underscore the importance of multidisciplinary coordination and long-term follow-up to optimize outcomes in this rare pediatric cohort.